GLP-1 agonists in anaesthetic practice - a review of clinical data and recommendations - Pokrywka, Natalia; Polak, Marcelina; Suwała, Dawid; Hetnar, Paulina; Fortuna, Milena; Kiper, Sebastian; Toczek, Sławomir; Tomala , Magdalena; Jastrowicz-Chęć, Katarzyna; Koryszko, Klaudia (Journal of Education, Health and Sport, 2025)
Abstract Introduction: Glucagon-like peptide-1 receptor agonists (GLP-1 RA) are a group of drugs originally used for the treatment of type 2 diabetes and now also for obesity and off-label indications. With the increasing popularity of the use of these substances, the likelihood of encountering such a patient in the operating theatre is increasing, creating new challenges for anaesthetic practice. Purpose: The aim of the following paper is to review current clinical data on patients using GLP-1 agonists in perioperative care and to provide recommendations from scientific societies for the management of these patients. Materials and research methods: The article is based on an analysis of research available on PubMed and Google Scholar. A literature review was conducted using the following keywords and medical subject headings: glucagon-like peptide-1 agonists; GLP-1 RA; perioperative period; gastric emptying; preoperative management; aspiration. The analysis included clinical trials, systematic reviews and expert consensus statements. Results: GLP-1 analogues show a number of beneficial metabolic, cardioprotective and nephroprotective effects, which may improve the overall health of patients. At the same time, these drugs, by delaying gastric emptying, increase the risk of regurgitation and pulmonary aspiration during induction of anaesthesia. Conclusion: Despite the growing population of patients using GLP-1 agonists, there are still no detailed reports on the basis of which guidelines for ideal management can be developed. Therefore, despite the existence of general recommendations from societies, special caution and an individual approach when working with such patients is advisable.